Enhancing Teamwork and Clinical Competence in Radiotherapy Education: Integrating TeamSTEPPS with PEARLS Structured Debriefing in Scenario-Based Simulations - Liu G; Lan T; E M; He Y; Hu H (Advances in Medical Education and Practice, 2025)
Guohui Liu,1 Tian Lan,2 Mingyan E,1 Yunlong He,1 Hanqing Hu3 1Department of Radiation Oncology, Harbin Medical University Cancer Hospital, Harbin, 150040, People’s Republic of China; 2Department of Educational Administration, Harbin Medical University Cancer Hospital, Harbin, 150040, People’s Republic of China; 3Department of Colorectal Cancer Surgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, 150086, People’s Republic of ChinaCorrespondence: Hanqing Hu, Department of Colorectal Cancer Surgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, 150086, People’s Republic of China, Email huhanqing@hrbmu.edu.cnObjective: This study aimed to evaluate whether integrating the TeamSTEPPS model with PEARLS structured debriefing improves teamwork competencies and clinical decision-making among radiotherapy residents, compared to traditional simulation teaching, and to assess its broader applicability in medical education.Methods: From June to December 2023, 36 standardized training residents from the Radiotherapy Department of Harbin Medical University Cancer Hospital were selected and randomly assigned to an experimental group and a control group, each with 18 participants, using a random number table The experimental group underwent scenario-based simulation teaching incorporating the TeamSTEPPS model and PEARLS structured debriefing, while the control group received traditional simulation teaching. Post-intervention, a unified quantitative assessment evaluated theoretical knowledge, skill performance, and simulation performance in both groups. Additionally, satisfaction levels were assessed via questionnaire.Results: The experimental group exhibited significantly higher scores in theoretical knowledge (88.55± 6.52) and skill performance (87.68± 18.42) compared to the control group (71.63± 5.69 and 58.96± 11.47, respectively; P< 0.05). The experimental group exhibited statistically significant improvements in teamwork competencies, including communication (23.22± 2.21 vs 21.43± 3.77, P< 0.05), leadership (23.40± 2.22 vs 22.19± 3.51, P< 0.05), situational awareness (18.95± 1.61 vs 17.62± 2.64, P< 0.05), and mutual support (27.93± 2.92 vs 25.69± 5.76, P< 0.05). The experimental group’s higher satisfaction (94.44% vs 77.78%, P< 0.05) underscores the potential of this integrated approach to address systemic challenges in clinical education, such as fragmented teamwork training and insufficient reflective practice. These findings suggest that combining TeamSTEPPS with PEARLS could serve as a replicable framework for multidisciplinary medical training programs aiming to enhance both technical proficiency and collaborative care.Conclusion: The innovative combined teaching method applied in this study to scenario-based simulation teaching in radiation oncology can significantly enhance residents’ theoretical knowledge, skill performance, and team collaboration abilities.This methodology exhibits notable advantages in clinical teaching within the radiotherapy department and with potential applicability to multidisciplinary medical education and standardized residency programs.Keywords: radiation oncology, teaching methods, resident standardized training, simulation teaching, team collaboration